EDUKASI MIKTIGASI BANJIR BERBASIS AUGMENTED REALITY UNTUK KOMUNITAS BERKELANJUTAN - Dewi Purnamasari; Soraya Rosna Samta; Rizal Ichsan Syah Putra; Nelly Zulfa; Ahmad Riki Andreas (Abdi Masya, 2026)
Community education on flood disaster mitigation often faces challenges because conventional methods are less interactive. This community service program aims to enhance disaster literacy and preparedness within community groups through innovative, technology-based educational media. The method employed was participatory training, with lectures, interactive discussions, and a primary focus on demonstrating and using an Augmented Reality (AR) application specifically designed for flood-mitigation simulation. The activity was attended by 30 members of a women's community empowerment group. The results indicated a significant increase in participants' understanding, as measured by pre- and post-tests, with the average score rising from 52.5 to 87.8. Qualitative feedback also revealed high enthusiasm, with 95% of participants stating that the AR-based learning method was more engaging and easier to understand than traditional counseling. The conclusion of this program is that AR technology is highly effective as a medium for participatory education in improving community preparedness for flood disasters. This innovative approach is recommended.